PERSEPSI ORANGTUA TERHADAP PROGRAM KHUSUS PENGEMBANGAN DIRI BAGI ANAK TUNAGRAHITA - Nafisa, Adila; Marlina, Marlina (STKIP Pesisir Selatan, 2024)
This research is motivated by the fact that some parents still do not understand the special self-development program for mentally retarded children so that parents still do not understand the extent to which their children's abilities have been achieved in aspects of the special self-development program for mentally retarded children. This research aims to determine parents' perceptions of their children's achievement of abilities in aspects of special self-development programs for mentally retarded children. This research uses quantitative descriptive methods. The results of this research show parents' perceptions of the achievement of children's abilities in aspects of special self-development programs for mentally retarded children, namely the self-care aspect is in the quite good category with a percentage of (75,8%), the self-care aspect is in the quite good category with a percentage of (66,7%), the self-help aspect is in the quite good category with a percentage (56,7%), the communication aspect is in the poor category with a percentage (48,5%), the socializing aspect is in the poor category with a percentage (45,5% ), aspects of daily living skills are in the quite good category with a percentage of (57,6%), aspects of filling free time are in the quite good category with a percentage of (66,7%).